Microbiological analysis after complete or partial removal of carious dentin using two different techniques in primary teeth: A randomized clinical trial - Deepak Kumar Singhal; Shashidhar Acharya; Arun Singh Thakur (Wolters Kluwer Medknow Publications, 2016)
Background: The management of deep carious lesions can be done by various techniques but residual caries dilemma still persists and bacterial reduction in cavities treated by either partial or complete caries removal techniques is debatable. So the objective of the present randomized clinical trial was to compare microbial counts in cavities submitted to complete caries removal and partial caries removal using either hand instruments or burs before and after 3 weeks of restoration. Materials and Methods: Primary molars with acute carious lesions in inner half of dentine and vital pulp were randomly divided into three groups of 14 each: Group A: Partial caries removal using hand instruments atraumatic restorative treatment (ART) only; Group B: Partial caries removal using bur; Group C: Complete caries removal using bur and caries detector dye. Dentine sample obtained after caries removal and 3 weeks after restoration, were subjected to microbial culture and counting (colony-forming units [CFU]/mg of dentine) for total viable bacterial count, Streptococcus spp., mutans streptococci, Lactobacillus spp. Results: Three techniques of caries removal showed significant (P < 0.05) reduction in all microorganisms studied after 3 weeks of evaluation, but there was no statistically significant difference in percentage reduction of microbial count among three groups. Conclusion: Results suggest the use of partial caries removal in a single session as compared to complete caries removal as a part of treatment of deep lesions in deciduous teeth in order to reduce the risk of pulp exposure. Partial caries removal using ART can be preferred for community settings as public health procedure for caries management.